2009
DOI: 10.1097/scs.0b013e3181acdc05
|View full text |Cite
|
Sign up to set email alerts
|

Prefabricated Scalping Forehead Flap With Skeletal Support

Abstract: It is difficult to reconstruct a nose with adequate shape, color, and texture in patients who have full-thickness nasal defects with extensive loss of skeletal support. The scalping forehead flap is a reliable technique for nasal reconstruction. To our knowledge, however, there have been no reports about a prefabricated scalping forehead flap with a bone graft as skeletal support. In the case reported here, a prefabricated scalping forehead flap combined with an iliac bone graft as skeletal support was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Nowadays, as an objective, non‐invasive and real‐time approach, near infrared imaging has attracted much attention [23–26]. Previous studies have shown that it has been broadly used in lymphangiography, angiography, sentinel lymph nodes, tumor margin detection and so on [27–29]. More importantly, these results also show that NIR‐II imaging has advantages over traditional NIR‐I imaging in clinical scenarios based on its advantages in depth sensitivity, higher spatial resolution and improved signal‐to‐noise ratio [8, 12, 13, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, as an objective, non‐invasive and real‐time approach, near infrared imaging has attracted much attention [23–26]. Previous studies have shown that it has been broadly used in lymphangiography, angiography, sentinel lymph nodes, tumor margin detection and so on [27–29]. More importantly, these results also show that NIR‐II imaging has advantages over traditional NIR‐I imaging in clinical scenarios based on its advantages in depth sensitivity, higher spatial resolution and improved signal‐to‐noise ratio [8, 12, 13, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an expanded flap may be considered for alternative delay procedures 12. We previously used delay of incisions on three sides in the forehead and lower leg regions,13–16 because we, as well as Tosun et al,6 consider that delay of incisions on three sides is effective to prevent critical congestion. In this case, delay of incisions on three sides was performed, although the blood flow to the most inferomedial part was likely to be tenuous, and critical congestion was successfully avoided.…”
Section: Discussionmentioning
confidence: 99%
“…However, in various case series and reports, diverse modifications for varying reconstructive needs have been described including single stage forehead flap passing the pedicle subcutaneously 2 , folded forehead flap 3 , split forehead flap 4 to reconstruct both eyelids defect simultaneously, prefabricated with cartilage grafts 5 , expanded forehead flap and delayed flap 6 . Each of these modifications is associated with complications, which may lead to unsatisfactory outcome.…”
Section: Introductionmentioning
confidence: 99%